PERSEPSI KESESUAIAN BANGUNAN CAGAR BUDAYA TOKO MERAH TERHADAP FUNGSINYA OLEH MASYARAKAT SEKITAR - Yeptadian Sari; Ari Widyati Purwantiasning (PROSIDING SNAST, 2018)
The suitability between building function and building type is very influential on the sustainability of that building, especially for historical buildings that should be preserved, it is like Toko Merah in Kota Tua Jakarta. The Toko Merah is a cultural heritage building which means that the building must be protected, preserved and the façade building cannot be changed, which is allowed only to reuse it or so-called Adaptive Re-Use. Currently the Toko Merah serves as a meeting or wedding hall. This study finds out the suitability of the current Toko Merah’s function as a meeting or wedding hall based on the perception of the community surrounding that heritage building. This research is an explorative research with statistical descriptive analysis method. The method of determining the sample by purposive sampling, data collection technique is survey by means of data collection that is questioner. The results of this study said 70% of the respondents stated that the Toko Merah is not suitable to be used as a meeting hall and wedding building.